Development of Risk Coefficient for Input to New Indonesian Seismic Building Codes - Sengara, I Wayan; Sidhi, Indra Djati; Mulia, Andri; Asrurifak, Muhammad; Hutabarat, Daniel (Journal of Engineering and Technological Sciences, 2016)
In 2010 a national team (Team 9) developed the hazard curve and maximum considered earthquake (MCE) for the whole Indonesian area. The results were further applied in this study. Risk-targeted ground motions (RTGM) with 1% probability of building collapse in 50 years were developed by integrating the hazard curve with the structural capacity distribution. Parametric study on various variables that affect the log-normal standard deviation suggests a value of 0.7. In the effort to obtain the RTGM for the whole Indonesian region, integration was carried out using definite integration in which the curves are split into thin vertical strips and the areas below each curve are multiplied and summed. Detailed procedures and verification are given in this paper. An example of RTGM calculation was carried out for Jakarta City and then applied to the whole Indonesian region. Risk coefficients defining the ratio between RTGM and MCE were eventually developed and mapped. Risk coefficient development was generated for two periods of interest, i.e. a short time period (T = 0.2 seconds) and a 1-second period, respectively. Based on the results, for the period of 1.0 seconds 55% of Indonesian cities/districts have a risk coefficient in the range of 0.9 to 1.1 and about 37% in the range of 0.7 to 0.9, with only 5% in the range of 1.1 to 1.25.